Implementasi Kebijakan Distribusi dan Pemetaan Kualifikasi Tenaga Pendidik di Lingkup Dinas Pendidikan Nasional, Pemuda dan Olahraga Kabupaten Tulang Bawang - Azima Dimyati (e-JKPP, 2015)
Problem of this research is How implementation of policy of distribution of energy of the education and First Middle mapping kualifikasi schoolteacher this Research Type is research qualitative by using descriptive analysis qualitative. this Method use is to mendeskripsikan of implementation of policy of distribution of energy of the education and First Middle mapping kualifikasi schoolteacher in Regency of Tulang Bawang. All data obtained is direct the than field informan by using interview and obsevasi.Result of research indicate that the implementation of policy of distribution of energy of the education and First Middle mapping membership schoolteacher in Regency of Tulang Bawang have walked, but not yet optimal of the mentioned happened by because (1) Distribution learn the Public Servant of Civil of Junior High School not yet flattened between school of exist in existing school and urban of countryside. To fill the insuffiency learn at school countryside hence side On duty Education of Young fellow and Athletics of Regency of Tulang Bawang lift the teachers assistive to fill the insuffiency learn at school countryside, but not yet answered the demand the requirement learn because a lot of teacher assistive which is only enlisted at certain school but do not run the duty. (2) Map membership learn the perbidang study not yet flattened between Junior High School of exist in urban answer the demand the amount learn the study area, while existing Junior High School of countryside not yet as required with the background of teacher education,so that still a lot of teacher of at countryside school teaching disagree with education background it.